Immunocytochemical identification and ontogeny of adenohypophyseal cells in a cave fish, Phreatichthys andruzzii (Cypriniformes: Cyprinidae). Issue 5 (1st February 2017) - Grandi, G.; Pezzi, M.; Marchetti, M. G.; Chicca, M.
Abstract : The morphogenesis of the pituitary gland and the chronological appearance of adenohypophyseal cells were investigated for the first time in the Somalian cave fish Phreatichthys andruzzii by immunocytochemistry. The adult adenohypophysis contained: a rostral pars distalis, with prolactin (PRL) cells arranged in follicles and adrenocorticotropic (ACTH) cells, a proximal pars distalis with somatotropic (GH), β‐thyrotropic (TSH), β‐gonadotropic type I (FSH) and type II (LH) cells and a pars intermedia with α‐somatolactin (SL), α‐melanotropic (MSH) and β‐endorphin (END) cells. All regions were deeply penetrated by neurohypophyseal branches. At hatching (24 h post‐fertilization) the pituitary was an oval cell mass, close to the ventral margin of diencephalon. The first immunoreactive cells appeared as follows: PRL at 0·5 days after hatching (dah), GH and SL at 1·5 dah, END at 2 dah, TSH, ACTH and MSH at 2·5 dah, FSH at 28 dah and LH at 90 dah. The neurohypophysis appeared at 5 dah and branched extensively inside the adenohypophysis at 130 dah, but there was no boundary between rostral pars distalis and proximal pars distalis at this stage. The potential indices of prolactin and growth hormone production increased until 28 and 60 dah, respectively. The potential index of growth hormone production correlated positively with total length. Activity of PRL and GH cells, measured as ratio of cell area to nucleus area, was significantly higher in juveniles than in larvae.